Leading with heart: academic leadership during the COVID-19 crisis. (June 2021) - Lawton-Misra, Nita; Pretorius, Tyrone
The COVID-19 pandemic has impacted every sphere of life. It has brought into sharp focus not only the critical role that leaders have to play in taking charge of their organisations and employees, but the complexity of that leadership role, too. The authors of this paper are both psychologists who occupy leadership positions in a university. The paper briefly explores the evolution of leadership theory, leadership in times of crises, generally, and leadership during the time of COVID-19. In addition, one of the authors offers a personal note on the leadership experience during COVID-19. What became clear during the reflections was that empathy, vulnerability, self-awareness and agility were some of the qualities needed during this crisis. In addition, the psychodynamic concept of containment appears very relevant in managing the affective intensity experienced by staff and students. Leaders were expected to not only fully understand the meaning of empathy and compassion, but to know how to sincerely demonstrate these qualities to staff and students alike. While these qualities should be expected of all leaders at all times, the pandemic brought them into sharper focus. We believe that we have benefitted from our training in psychology as these qualities of caring, empathy and self-awareness are embedded and sharpened in our training programmes.